Sport osób z niepełnosprawnością - przełamywanie barier = Sport of people with disabilities - breaking the barriers - Dalecka, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Disability does not exclude people from normal perception of the world, from expressing their wishes, needs and desires. The respondents in the autor`s research are only a small part of people with disabilities, they want to compete, participate in competitions and achieve their small and great successes.
Keywords: sport of disabled people; physical activity; disability; social exclusion; sport osób z niepełnosprawnościami; aktywność fizyczna; niepełnosprawność; wykluczenie społeczne